2007
DOI: 10.1186/1471-2334-7-146
|View full text |Cite
|
Sign up to set email alerts
|

The role of resuscitation promoting factors in pathogenesis and reactivation of Mycobacterium tuberculosis during intra-peritoneal infection in mice

Abstract: Background: Mycobacterium tuberculosis can enter into a dormant state which has resulted in one third of the world's population being infected with latent tuberculosis making the study of latency and reactivation of utmost importance. M. tuberculosis encodes five resuscitation promoting factors (Rpfs) that bear strong similarity to a lysozyme-like enzyme previously implicated in reactivation of dormant bacteria in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…Recently, it has been found that bacteria possess a specific system for autoregulation of growth and development, which participates in control of cell differentiation at the level of regulation of the functional activity of subcellular components and of the cell as a whole (Shleeva et al, 2010). Resuscitation-promoting factors have also been identified and their role in latency and reactivation of tuberculosis have been investigated (Biketov et al, 2007;Zhang et al, 2001;). Five genes encoding Rpf-like proteins have been found in M. tuberculosis genome, which may act in reactivation of "nonculturable " forms of M. tuberculosis (Kana et al, 2008;Mukamolova et al, 2002;Tufariello et al, 2004).…”
Section: Reversion Of Mycobacterial L-forms To Classical Tb Bacillimentioning
confidence: 99%
“…Recently, it has been found that bacteria possess a specific system for autoregulation of growth and development, which participates in control of cell differentiation at the level of regulation of the functional activity of subcellular components and of the cell as a whole (Shleeva et al, 2010). Resuscitation-promoting factors have also been identified and their role in latency and reactivation of tuberculosis have been investigated (Biketov et al, 2007;Zhang et al, 2001;). Five genes encoding Rpf-like proteins have been found in M. tuberculosis genome, which may act in reactivation of "nonculturable " forms of M. tuberculosis (Kana et al, 2008;Mukamolova et al, 2002;Tufariello et al, 2004).…”
Section: Reversion Of Mycobacterial L-forms To Classical Tb Bacillimentioning
confidence: 99%
“…In one study of mice infected with rpf double deletion mutants via the respiratory tract, only the DrpfAB mutant showed lower lung and spleen colony forming units (CFUs) versus the wild type Mtb strain (Russell-Goldman et al, 2008). This contrasts with an intraperitoneal model of infection where DrpfAC was more attenuated for growth than DrpfAB although differences in host, strain or experimental conditions may account for this (Biketov et al, 2007). With triple rpf deletion mutants, the loss of rpfB from a DrpfAC mutant was more attenuating for growth in the mouse lung than rpfD loss (Downing et al, 2005).…”
Section: Rpf Are Critical For Mtb Replication and Reactivation In Vivomentioning
confidence: 55%
“…When single rpf genes are deleted, there is no impact on the course of acute infection or the immunopathology witnessed, perhaps indicating physiological redundancy (Gupta & Srivastava, 2012). However, further deletion of rpf genes reduces Mtb virulence which manifests as reduced growth and dissemination from the site of primary infection (Biketov et al, 2007;Kana et al, 2008;Kondratieva et al, 2011;Russell-Goldman et al, 2008). Ultimately, the mortality of mice infected with attenuated rpf deletion mutants is lower (Kondratieva et al, 2011;Russell-Goldman et al, 2008).…”
Section: Rpf Are Critical For Mtb Replication and Reactivation In Vivomentioning
confidence: 99%
See 2 more Smart Citations